PENGARUH KEMAMPUAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA III - Rukmini; Lubis, Ahmad Taufik; Harahap , Nur Ain (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2022)
Perkebunan Nusantara III is a company engaged in oil palm plantations, where employee performance is very important for the progress of the company. The purpose of this study was to determine whether the ability and motivation affect the performance of employees at PT. Nusantara Plantation III. The population of this study amounted to 392 employees. The sample of this research is random sampling using Sugiyono's theory, if the subject is less than 100, it is better to take all of them. So the sample in this study was taken 15% of the total population, namely 60 employees, the data collection used was by using a questionnaire given randomly to the respondents. Data using SPSS version 21.0 for windows. Results Based on the research, the validity test was declared valid becausethe value of rcount > rtable, the reliability test was accepted because the alpha coefficient was above 0.60, the results of the multiple linear regression equation test were Y= 8.020 + 0.756 + 0.072 + e had a positive and significant effect on employee performance, the test it is known that the sig value for the effect of X1 on Y is 0.000 < 0.05 and X2 on Y is 0.165 > 0.05, the coefficient of determination (R2) is obtained by an R Square value of 0.734, this means that the influence of X1 and X2 variables is simultaneous effect on variable Y is equal to 0.73%.